SAFETY FIRST: ABOUT ECONOMIC RISKS AND FUTURE THREATS FOR THE DEVELOPMENT OF DIGITAL TECHNOLOGIES - E. Karpunina; S. Moiseev; E. Lisova; A. Beilina (Вестник Северо-Кавказского федерального университета, 2022)
Modern development of society is inextricably linked with digital technologies and high level of informatization. Under their influence, new economic conditions are formed, which, in turn, determine a number of changes in the life of all subjects of economic relations. This article shows the effects of digitalization in the process of entering the digital space of the world and the formation of digital economies. All the effects of digitalization depending on their impact on the economic security of the state, the authors are conditionally divided into positive and negative, as well as analyzed the economic, technological and social effects of digital development. The concept of mutual influence of digital economy, institutional changes and economic security is offered, and also character of their interrelations is defined. It is determined that risks and threats to economic security can limit the development of the economic system of the state and neutralize the positive effects of digitalization. The necessity of detailed development ofmethods and tools for ensuring economic security at all levels of management on the basis of institution-building is substantiated.